PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA DI SMP SWASTA KAMPUS PADANGSIDIMPUAN - Harahap, Haritsah Hammamah (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2021)
This study aims to determine the extent of the influence of the blended learning model on the creative thinking ability of students on the subject of straight-line equations in class VIII of Private Junior High School, Padangsidimpuan Campus. This type of research is an experimental research designed in a one group pretest posttest design model. The population in this study were all eighth grade students of the Padangsidimpuan Private Junior High School, as many as 136 students consisting of 4 classes. The sample is part of the population that is considered to represent the population to be used as a source of data or information in a study. The sampling technique used is cluster random sampling where each class has the same opportunity to become the research sample. The class that became the sample was class VIII-3, which consisted of 33 students. The results showed that students' mathematics learning outcomes using the blended learning model were higher with an average of 74.09 than students' mathematics learning outcomes using direct or face-to-face learning models with an average of 66.36. Based on the results of hypothesis testing at a significance level of 5% using Minitab software, it can be concluded that there is an effect of the blended learning learning model on the creative thinking ability of students on the subject of straight line equations in class VIII of Private Junior High School, Padangsidimpuan Campus.